PERLINDUNGAN KONSUMEN TERHADAP KLAUSULA BAKU DALAM PERJANJIAN PENGIKATAN JUAL BELI RUMAH PERUSAHAAN LIPPO CIKARANG: Consumer Protection Against Standart Clauses In The House Sale And Purchase Binding Agreement Of The Lippo Cikarang Company - Rebecca Octania Br. Sitompul; Renti Maharaini Kerti (Reformasi Hukum Trisakti, 2025)
In relation to the process of purchasing a house, there is a document containing an agreement between the business actor and the consumer called the Sale and Purchase Binding Agreement (PPJB). This document is prepared by the developer and signed by the consumer. One common issue is that developers often include unfair or unbalanced clauses that harm consumer rights. Since the PPJB is drafted by the developer, their subjectivity and interests tend to dominate the agreement's content. The problem raised is whether the clauses in the PPJB comply with Law Number 8 of 1999 on Consumer Protection and what remedies consumers have against standard clauses that violate this law. This study uses a normative research method with secondary data and a descriptive-analytical approach. The analysis is conducted qualitatively, with conclusions drawn using deductive logic. The research result and conclusions indicate that several articles in the PPJB drafted by PT Lippo Cikarang do not comply with regulations. Consumers who feel disadvantaged can seek legal recourse through litigation by filing a lawsuit or through non-litigation methods by submitting complaints to the Consumer Dispute Resolution Agency (BPSK), the National Consumer Protection Agency (BPKN), and the Consumer Protection Non-Governmental Organization (LPKSM).